A review of resource needs in postgraduate studies - Zainal Abiddin, Norhasni; Mohd Ayub, Ahmad Fauzi; Kamarudin, Nurzatulshima (Department of History Education, Indonesia University of Education, 2009)
The desire to pursue higher education is constantly increasing. The government and the institutions of higher learning are striving to attract more students, especially at the graduate level by making every effort to provide quality education. Some scholars proposed that the strategic success of a service organization depends on its ability to consistently meet or exceed customer service expectations. Students as institutions' customer, need information and support to cope in balancing the demands of the different environments. One of the major problems facing by the higher education nowadays is attrition and completion rates. To manage this issue, a constant effort should be made. The resources offered by the institution determine the ability of the institution to manage their students effectively. The main thrust of this paper is to provide the relevent input for resource development in institutional of higher education. It is hoped to assist the institution to identify and address implementation issues related to postgraduate studies. The major contribution of this review is the guideline for effective resource and in developing distinguished human capital.